2016
DOI: 10.3892/ol.2016.4617
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of TLR7 in gastric cancer tissues and the effects of TLR7 activation on gastric cancer cells

Abstract: Abstract. The present study aimed to determine the expression of Toll-like receptor 7 (TLR7) in gastric cancer tissues and investigate the effects of its activation on gastric cancer cells. Patients with gastric cancer (n=30) and patients without gastric cancer (control; n=14) who underwent gastroscopy were enrolled in the study. Gastric cancer and cancer-adjacent tissues were obtained from the patients with gastric cancer, and normal gastric epithelial tissues were obtained from the control patients. The TLR7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…TLR7 was previously thought to reduce the viability of gastric cancer cells 15 . Accordingly, we found that prognosis was better amongst patients with a high TLR7 expression in several subgroups, particularly among those with locally advanced disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TLR7 was previously thought to reduce the viability of gastric cancer cells 15 . Accordingly, we found that prognosis was better amongst patients with a high TLR7 expression in several subgroups, particularly among those with locally advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…TLR-related therapy, particularly TLR agonists, capable of activating the immune system against cancer have been broadly studied in several malignancies 18,19 . The administration of a TLR7 agonist, imiquimod, increases the expression of TLR7 in gastric cancer cells and reduces their viability 15 . Whether imiquimod has direct cytotoxic effects or if acting via the modulation of inflammatory cell activity remain incompletely understood since numerous different pathways are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study found that GC patients with high TLR5 tissue expression can have a better prognosis, particularly who has stage II disease or intestinal-type GC (Kasurinen et al, 2019). Studies have explored that TLR7 expression is low in GC tissues, and stimulating TLR7 could promote the secretion of pro-inflammatory cytokines, and inhibit the proliferation of GC cells (Jiang et al, 2016). Thus, it can be seen that the function of different TLRs in GC is complex and different.…”
Section: Tlr Structure and Signaling Pathwaysmentioning
confidence: 99%
“…TLR7 is expressed on the endosomal membrane (Takeda and Akira, 2015). TLR7 was found low expressed in GC tissues (Jiang et al, 2016). Activating TLR7 can strengthen anti-cancer immunity.…”
Section: Tlr7mentioning
confidence: 99%